Cidadania global e formação docente para a cidadania global: construindo pontes e conectando mundos rumo à cidadania planetária - Francesco, Cristina Lage de (2020)
The objective of this study is to describe and interpret the phenomenon teacher education for Global citizenship, understood as a phenomenon of human experience. In order to achieve it, the following research question is considered: What is the essence of Teacher education for global citizenship? The investigated phenomenon is understood from the perspective of the subjects who experience it, that is, six in-service teachers. From the perspective of their varied teaching profiles, this research presents an interpretation of teacher education that enables critical reflections about the construction of a professional profile that takes into account the education of individuals who are pro-active contributors to a fairer, safer, more peaceful, tolerant, inclusive, and sustainable world. Theoretically, it seeks to articulate the view of the participating teachers with the notion of global citizenship proposed by UNESCO (2014, 2015), of planetary citizenship proposed by Morin (2010, 2013, 2015) and of teachers’ education, from the perspective of Moraes (1997, 2008, 2012) and of Freire (2013) and Freire and Leffa (2013), which were all considered from Morin’s complex thought perspective (2003, 2007, 2015). Methodologically, this research is anchored in a qualitative proposal, which is guided by the Complex Hermeneutic-Phenomenological Approach (CHPA), as suggested by Freire (2010, 2011, 2017), and counts on the following instruments for recording texts: questionnaire, reflective diary, lesson observations and hermeneutic conversations. The development of this research suggests that the comprehension of Global citizenship as a phenomenon of human experience preceeds the comprehension of teacher education for global citizenship, hence the natural unfolding of this research into two phenomena. My investigation demonstrates that the essence of the phenomenon global citizenship reveals itself through the following complex hermeneutic-phenomenological themes: enlargement, transcendence, construction/ deconstruction, respect, awareness and English. As for the phenomenon teacher education for global citizenship, it reveals itself through the themes: process, knowledge, awareness, questioning, iniciative, lack and webs. Reflecting upon both phenomena in light of the epistemology of complexity, I realize that the concept of planetary citizenship is more relevant and pertinent than global citizenship